Effects of drought and prescribed fire on energy exchange in longleaf pine ecosystems. Issue 7 (31st July 2015) - Whelan, Andrew; Starr, Gregory; Staudhammer, Christina L.; Loescher, Henry W.; Mitchell, Robert J.
Abstract : The structure and function of longleaf pine savanna ecosystems is regulated by cyclic fire, yet there is a lack of understanding about how the frequency of fire influences longleaf pine ecosystem energy dynamics. There are further uncertainties in how predicted changes in temperature and precipitation may affect the interaction between fire and energy exchange in these ecosystems. We investigated energy dynamics in three frequently burned longleaf pine ecosystems along a gradient of soil moisture availability using eddy covariance techniques. We analyzed sensible energy ( H ), latent energy (LE) and soil heat flux ( G ) over time since fire, using micrometeorological variables as covariates. Based on statistical tests of autocorrelation, data were analyzed as 30‐day averages with general linear models. Over three years of measurement, we found that sensible energy, latent energy and soil heat flux recovered to pre‐fire rates within one month following prescribed fire. Changes in water availability associated with drought over the study period had a stronger influence on energy dynamics than did fire. When precipitation was near long‐term averages, annual evapotranspiration (ET) was 743, 816 and 666 mm y −1 at the mesic, intermediate and xeric sites, respectively. During extreme drought, annual ET decreased 4 and 7% at the xeric and intermediate sites, to 754 and 642 mm y −1, respectively, and decreased 20% at the mesic site, to 594 mm y −1 . Similarly, Bowen ratios were up to two times higher during drought years versus those with average precipitation. These frequently burned longleaf pine ecosystems are known to be well adapted to fire. The more xeric the site, the more resilient they were to drought, suggesting adaptations of this ecosystem maintained higher levels of physiological activity. This three‐year study begins to illuminate longleaf pine ecosystem energy dynamics, however long‐term observations over a greater range of environmental conditions are necessary to increase our knowledge of the complex interactions between fire, climate and energy dynamics in these ecosystems.